2021
DOI: 10.1155/2021/3298400
|View full text |Cite
|
Sign up to set email alerts
|

Trilobatin Alleviates Cognitive Deficits and Pathologies in an Alzheimer’s Disease Mouse Model

Abstract: Alzheimer’s disease (AD) is the most common neurodegenerative disease nowadays that causes memory impairments. It is characterized by extracellular aggregates of amyloid-beta (Aβ), intracellular aggregates of hyperphosphorylated Tau (p-Tau), and other pathological features. Trilobatin (TLB), a natural flavonoid compound isolated from Lithocarpuspolystachyus Rehd., has emerged as a neuroprotective agent. However, the effects and mechanisms of TLB on Alzheimer’s disease (AD) remain unclear. In this research, dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 39 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Trilobatin ( Figure 4 ) is a dihydrochalcone compound distributed in Lithocarpuspolystachyus Rehd., and has anti-neuroinflammatory effects. Trilobatin is reported to improve cognitive impairment, reduce activated microglia and astrocytes with decreasing Iba-1 and GFAP expression, and inhibit the secretion of TNF-α, IL-1β and IL-6 in the hippocampus from APP/PS1 and triple-transgenic-induced AD mice through the down-regulation of HMGB1, TLR4, MyD88, TRAF6 and p-p65 ( 142 , 143 ). Moreover, in OGD/R-stimulated astrocytes and the brain of MACO-induced I/R rats, trilobatin reduces the production of iNOS, and suppresses the activation of microglia and astrocytes via up-regulating Nrf2, HO-1, NQO1 and SIRT3 protein, as well as suppressing p65 phosphorylation and the expression of Keap1, TLR4, MyD88, and TRAF6 ( 144 ).…”
Section: Effects Of Natural Flavonoids On Neuroinflammationmentioning
confidence: 99%
“…Trilobatin ( Figure 4 ) is a dihydrochalcone compound distributed in Lithocarpuspolystachyus Rehd., and has anti-neuroinflammatory effects. Trilobatin is reported to improve cognitive impairment, reduce activated microglia and astrocytes with decreasing Iba-1 and GFAP expression, and inhibit the secretion of TNF-α, IL-1β and IL-6 in the hippocampus from APP/PS1 and triple-transgenic-induced AD mice through the down-regulation of HMGB1, TLR4, MyD88, TRAF6 and p-p65 ( 142 , 143 ). Moreover, in OGD/R-stimulated astrocytes and the brain of MACO-induced I/R rats, trilobatin reduces the production of iNOS, and suppresses the activation of microglia and astrocytes via up-regulating Nrf2, HO-1, NQO1 and SIRT3 protein, as well as suppressing p65 phosphorylation and the expression of Keap1, TLR4, MyD88, and TRAF6 ( 144 ).…”
Section: Effects Of Natural Flavonoids On Neuroinflammationmentioning
confidence: 99%
“…TLR-4 was upregulated in the brains of AD patients and an AD mouse model ( Walter et al, 2007 ; Figure 1 ). It was recently shown that trilobatin a flavonoid isolated from Lithocarpus polystachyus Rehd, trilobatin, had a neuroprotective effect In a murine model of AD (3×FAD) through TLR-4 inhibition ( Ding et al, 2021 ). In that study the interference with TLR-4 attenuated all the negative events associated with the AD model phenotype: Aβ burden, neuroinflammation, tau hyperphosphorylation, synaptic degeneration, hippocampal neuronal loss, and memory impairment ( Ding et al, 2021 ).…”
Section: Oligomers and Inflammationmentioning
confidence: 99%
“…It was recently shown that trilobatin a flavonoid isolated from Lithocarpus polystachyus Rehd, trilobatin, had a neuroprotective effect In a murine model of AD (3×FAD) through TLR-4 inhibition ( Ding et al, 2021 ). In that study the interference with TLR-4 attenuated all the negative events associated with the AD model phenotype: Aβ burden, neuroinflammation, tau hyperphosphorylation, synaptic degeneration, hippocampal neuronal loss, and memory impairment ( Ding et al, 2021 ). This and several other similar findings indicate that targeting TLR-4 might be an interesting therapeutic approach to AD ( Rahimifard et al, 2017 ; Paudel et al, 2020 ; Connolly et al, 2021 ).…”
Section: Oligomers and Inflammationmentioning
confidence: 99%
“…Of note, previous studies have revealed that TLB effectively attenuated cerebral ischemia-reperfusion injury due to its antioxidant properties and anti-inflammatory activities through activation of SIRT3 activity and inhibition of TLR4 signaling pathway [25]. Recently, preliminary experiments suggested that TLB supplementation efficiently prolonged lifespan of Caenorhabditis elegans in an anti-oxidative stress-dependent fashion, reduced Aβ 25-35 -induced HT22 cell apoptosis and alleviated cognitive deficits in 3×FAD AD animal model [26][27][28]. However, to date, there is no comprehensive description about the detailed mechanism of TLB on AD, and whether TLB can penetrate the BBB and the reciprocity between HMGB1 and SIRT3 is involved in the beneficial effects of TLB on AD still remains a mystery.…”
Section: Introductionmentioning
confidence: 99%